Physiological Responses of the Firefly Pyrocoelia analis (Coleoptera: Lampyridae) to an Environmental Residue From Chemical Pesticide Imidacloprid - Wang, Yi-zhe; Cao, Cheng-quan; Wang, Dun (Frontiers in Physiology, 2022)
Imidacloprid, a neonicotinoid insecticide, is widely applied to control insect pests across a broad spectrum. Though the impact of residues from this chemical pesticide on non-target organisms in the field has been reported, it was not well characterized across a wide range of ecosystems, especially for some species considered as environmental indicators that live in forests. The effects of sublethal dose of imidacloprid on firefly, Pyrocoelia analis, were analyzed physiologically and biochemically in this study to better understand the impact of chemical pesticide application on environmental indicators such as fireflies. After imidacloprid treatment, the midgut tissues of the larva presented an abnormal morphology featured as atrophy of fat body cells, shrinking cells, and the destruction of a midgut structure. The activities of antioxidant enzymes, superoxide dismutase, catalase, and peroxidase were noticeably increased during early exposure to sublethal imidacloprid and then decreased at later stages. The malondialdehyde content significantly increased after 12 h of exposure to imidacloprid compared with the control. Similarly, the enzyme activities of polyphenol oxidase and acetylcholinesterase were increased after the imidacloprid treatment and then decreased at the later stage. In summary, a sublethal dose of imidacloprid caused destructive change in the tissue structure, and this damage was followed by an excessive reactive oxygen species that could not be eliminated by antioxidant enzymes. Our results indicated that the residues of imidacloprid might cause severe toxicity to non-target insects in the environment even far away from the agro-ecosystem where the chemicals were applied.